Prognostic value of non-invasive right ventricle-pulmonary artery coupling in patients with pulmonary hypertension associated with left heart disease - Ling-Zhi Dou; Shan-Shan Li; Sen Wang; He Jiang; Yu-Li Zheng; Meng-Meng Duan; Yi-Gang Zhang; Bing Han; Jian-Ming Li; Hong-Yun Ruan (Journal of Cardiothoracic Surgery)
Abstract Objective This study aims to assess the prognostic significance of non-invasive right ventricle-pulmonary artery coupling in patients with pulmonary hypertension associated with left heart disease (PH-LHD) and identify the relevant clinical factors involved. Methods A cohort of 362 patients diagnosed with PH-LHD was included in this study. Plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels were measured using enzyme-linked immunosorbent assay (ELISA). Echocardiography was employed to screen routine ultrasound parameters. The tricuspid annular plane systolic excursion/pulmonary artery systolic pressure (TAPSE/PASP) and S’/PASP ratios were calculated. Participants were categorized into two groups based on the TAPSE/PASP ratio: moderate-to-severe and mild uncoupling groups. Both groups underwent routine follow-up for a period of 3 to 15 months. Clinical events included all-cause mortality, heart failure rehospitalization, and stroke. Clinical events were documented, and a multivariate Cox regression model evaluated the correlation between the TAPSE/PASP ratio and prognosis. The Kaplan-Meier survival analysis was also conducted. Results The moderate-to-severe uncoupling group exhibited significantly higher proportions of males; individuals with a history of smoking, valvular disease, diabetes mellitus, or stroke; and elevated levels of PASP, right ventricular diameter (RVD), left ventricular diameter (LVD), left ventricular end-diastolic (LVED), and lg (NT-proBNP) compared to the mild uncoupling group (P < 0.05). Conversely, parameters such as age, TAPSE, S’, S’ /PASP, and left ventricular ejection fraction (LVEF) were significantly lower in the moderate-to-severe uncoupling group compared to the mild uncoupling group (P < 0.05). Multivariate Cox regression analysis revealed that TAPSE/PASP (hazard ratio [HR] = 0.150, 95% confidence interval [CI] [0.023, 0.968], P = 0.046) was a protective factor for the recurrence of clinical events. In contrast, LVED (HR = 1.301, 95% CI (1.004, 1.059), P = 0.024) and lg (NT-proBNP) (HR = 1.870, 95%CI [1.304, 2.682], P = 0.001) were independent risk factors for the recurrence of clinical events. KaplanMeier survival analysis demonstrated that the mild uncoupling group exhibited a significantly higher overall survival rate compared to the moderate-to-severe uncoupling group (Log Rank P = 0.024). Conclusions The TAPSE/PASP ratio is a predictive marker for clinical outcomes in patients with PH-LHD.